Influence of the nature of the anchoring group on electron injection processes at dye–titania interfaces. Issue 43 (27th October 2017) - Arbouch, Imane; Cornil, David; Karzazi, Yasser; Hammouti, Belkheir; Lazzaroni, Roberto; Cornil, Jérôme
Abstract : DFT calculations show deep changes in the electronic and optical properties of oligothiophene dyes when grafted on a titania surface via carboxylic acid or catechol moiety as anchoring group. Abstract : We report (time-dependent) density functional theory calculations characterizing the changes in the electronic and optical properties of oligothiophene dyes when grafted on a titania surface via a carboxylic acid or catechol moiety as anchoring group, in relation to their use in dye-sensitized solar cells. The broadening of the LUMO level of the compounds upon adsorption has been extracted from the computed electronic structures and used to estimate electron injection times into the conduction band of the oxide. The strongly coupled carboxylic-containing dyes lead to faster electron injection times compared to catechol-substituted dyes. This difference is ascribed to the electron–donating character of the catechol moiety that polarizes the dye LUMO away from the dye@titania interface. The absorption spectra simulated at the TD-DFT level indicate that the grafted carboxylic–thiophene dyes undergo an indirect injection mechanism (type I) in which an intramolecular excitation is created before the charge is transferred to titania. In contrast, catechol dyes with a short conjugation length for the thiophene backbone are type II sensitizers exhibiting a direct injection mechanism leading to a direct photoexcitation from the dye HOMO to the titania conduction band. A mixed character prevails for the injection in the case of catechol dyes containing a longer oligothiophene chain.